PENDAMPINGAN PERENCANAAN KARIR SISWA DAN PENGEMBANGAN KARAKTER DI SD NEGERI TUGUREJO - Hijrah Eko Putro; Indiati Indiati; Desi Nur Anggreani; Agilia Putri Anggita Sari; Dano Rizal Wibowo; Bangkit Budi Laksono (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
Kanggotan is located in the area of Tugurejo Village, Tempuran District, Magelang Regency. Tugurejo Village has 2 educational institutions, MI Tugurejo and SD Negeri Tugurejo. Based on the results of observations and interviews with the principal, information was obtained that SD Negeri Tugurejo has a physical condition of the school that is not so large, the location is not strategic, and most students are from underprivileged family backgrounds with relatively low incomes, the purpose of this service is to develop the potential of children related to their interests and talents to have a good career plan and introduce various applications and websites to the teacher council. To bring an interesting teaching and learning process to students, especially about career planning. Efforts to overcome these problems include providing career planning guidance and improving students' life skills at SD Negeri Tugurejo as a provision for continuing their careers. The method of implementing the service is to provide career planning training to students and socialization of career planning to teachers and parents of students; the results of this service program are career learning media in the form of career snake and ladder games that can be used by teachers, making pamphlets of motivational words with the theme of career planning, the understanding of the mindset of students and parents of students towards career planning.